Combined Aerobic and Resistance Training Increases Stretch- Shortening Cycle Potentiation and Walking Economy in Postmenopausal Women - Singh, Harshvardhan; Carter, Stephen J.; Mathis, Shannon L.; Bryan, David R.; Koceja, David M.; McCarthy, John P.; Hunter, Gary R. (Frontiers in Physiology, 2019)
Purpose: Secondary analyses were performed to test whether combined aerobic and resistance training altered walking economy (i.e., net oxygen uptake) and/or stretch-shortening cycle potentiation (SSCP). A further objective was to determine if walking economy and SSCP were related before or after training. Methods: Ninety-two postmenopausal women were enrolled wherein 76 completed 16 weeks of supervised aerobic and resistance training. Participants were randomized to one of three training groups based on frequencies: a) 1 d∙wk-1 (n = 23); b) 2 d∙wk-1 (n = 30) or; c) 3 d∙wk-1 (n = 23). Following assessments were performed at baseline and post-training. Indirect calorimetry was used to measure maximal oxygen uptake (V̇O2max) and walking economy (submaximal V̇O2 – resting V̇O2) during a graded exercise test and steady-state treadmill task, respectively. SSCP was determined by measuring the difference between a concentric (CO) and counter-movement (CM) leg press throw. Results: V̇O2max, walking economy, CO and CM velocity were significantly improved (p < 0.05) for all training groups, however; no time by group interactions were observed. Paired t-tests revealed participants exercise training 2 d∙wk-1 exhibited a significant time effect for SSCP (+0.04 ± 0.09 ms-1; p = 0.03). At baseline, multiple linear regression showed a negative relationship between walking economy and SSCP (r = -0.22; p < 0.04) adjusted for relative proportion of V̇O2max. No such relationship was found post-training. Conclusion: Irrespective of training-frequency, 16 weeks of combined aerobic and resistance exercise training increased ease of walking and economy. Only participants exercising 2d∙wk-1 ¬¬exhibited improvement in SSCP.